Retrospective evaluation of indications and birth results of cesarean section due to ophthalmologic diseases - Coşkun, Bora; Özateş, Serdar; Coşkun, Buğra; Kıncı, Mehmet Ferdi; Şimşir, Coşkun (The European Research Journal, 2020)
Objectives: To investigate the outcomes of cesarean section due to ophthalmologic indications.Methods: This retrospective clinical study included 40,190 patients underwent cesarean section due to ophthalmological indications between January 2013 – August 2015 in MLP Care Group Hospitals (It includes 32 hospitals). Demographic data, ophthalmologic history and indications and surgical outcomes of caesarean section was assessed.Results: Of the 53 patients with caesarean delivery due to ophthalmologic indications, 32 (60.4%) had high degree myopia, 7 (13.2%) had degenerative myopia, 8 (15.1%) had history of ocular surgery, 2 (3.8%) had history of vitreoretinal surgery due to retinal detachment, 2 (3.8%) had glaucoma with uncontrolled intraocular pressure, 1 (1.9%) had retinitis pigmentosa and 1 (1.9%) had optic neuritis.Conclusions: Ratio of ophthalmic indications is small within all cesarean indications and further longitudinal studies are needed to prevent from unnecessary cesarean section.